Formation of the Methodology of the Project-Activity Game in Inclusive Higher Education - Glushchenko, Valery Vladimirovich (Indonesian Journal of Multidiciplinary Research, 2025)
Inclusive higher education faces challenges in engagement and skill development because traditional teaching methods often fail to accommodate diverse learning needs. The Project Activity Game (PAG) methodology integrates game-based and project-based learning to enhance student participation and real-world competency. This study aims to develop and implement PAG in inclusive post-industrial universities to improve the effectiveness of higher education during the transition to a new technological order. The research employed pedagogical, didactic, historical, systemic, and logical analysis to examine existing methodologies and establish the theoretical foundations of PAG. The study identified key risks and opportunities associated with its adoption in inclusive and project-based education. The results demonstrate that PAG enhances engagement, knowledge retention, and problem-solving abilities because it immerses students in interactive, competency-driven tasks. The findings confirm that PAG can bridge the gap between education and industry needs, improving career readiness and inclusion. This research contributes to the evolution of higher education pedagogy, making learning more adaptive and accessible.